Age and Cultural Gender Equality as Moderators of the Gender Difference in the Importance of Religion and Spirituality: Comparing the United Kingdom, France, and Germany - Robinson, Oliver (Journal for the scientific study of religion, 2019)
A range of research studies has found that women report greater importance of religion and spirituality in their lives than men do. This study extends the literature on this phenomenon, and the theories that aim to explain it, by looking at whether gender differences in the three European countries (the United Kingdom, France, and Germany) differ by adult age group (young adults 18-39, midlifers 40-59, and older adults 60+), and by the cultural gender equality of the countries in question. Participants provided data on the importance of religiosity and spirituality to their life. Significant gender differences were found within all three countries, for each of the three age groups. In line with predictions based on Global Gender Gap Report 2016, Germany showed the smallest difference, followed by France and the United Kingdom. Gender differences were smaller in the young adult samples than for midlife adults or older adults.